An anti-TGF-β antibody suppresses metastasis via cooperative effects on multiple cell compartments - Nam, Jeong-Seok (2008)
Overexpression of transforming growth factor β (TGF-β) is frequently associated with metastasis and poor prognosis, and TGF-β antagonism has been shown to prevent metastasis in preclinical models with surprisingly little toxicity. Here we have used the transplantable 4T1 model of metastatic breast cancer to address underlying mechanisms. We showed that efficacy of the anti-TGF-β antibody 1D11 in suppressing metastasis was dependent on a synergistic combination of effects on both the tumor parenchyma and microenvironment. The main outcome was a highly significant enhancement of the CD8+ T-cell mediated anti-tumor immune response, but effects on the innate immune response and on angiogenesis also contributed to efficacy. Treatment with 1D11 increased infiltration of NK cells and T cells at the metastatic site, and enhanced expression of coactivators (NKG2D) and cytotoxic effectors (perforin and granzyme B) on CD8+ T-cells. On the tumor cells, increased expression of an NKG2D ligand (Rae1γ) and of a death receptor (TNFRSF1A) contributed to enhanced immune cell-mediated recognition and lysis. The data suggest that elevated TGF-β expression in the tumor microenvironment modulates a complex web of intercellular interactions that aggregately promote metastasis and progression. TGF-β antibodies reverse this effect, and the absence of a major effect of TGF-β antagonism on any one cell compartment may be critical for a good therapeutic window and the avoidance of autoimmune complications.